Sosialisasi Cara Mendeteksi Kandungan Boraks pada Makanan Menggunakan Bahan Dapur - Rizkita, Aden Dhana; Julianti, Nurlita; Ayu, Putri Diah; Fathimah Azzahra, Erica Ardhana (Universitas Ekuitas Indonesia, 2023)
One of the dangerous food factors is the discovery of borax in food. Borax is a preservative that is not intended for food preservatives. Turmeric contains a curcumin compound which is capable of being an indicator for borax detection with color change parameters. The purpose of this research is to provide knowledge to the community around the campus to understand the method of early detection of borax on August 1, 2022 in the form of community service for the Bachelor of Pharmacy Study Program in the pharmaceutical chemistry scientific cluster. The method used is a lecture by giving a presentation of material related to borax followed by a demonstration of how to detect borax. The results of the service will have an impact on the knowledge of the community around the Stikes Bogor Husada campus about identifying food ingredients that contain borax in order to reduce the risk of exposure to borax by using turmeric which contains curcumin as a natural indicator of borax detection by providing an indicator of color change in food samples if it contains borax. The conclusion from this activity is that there is an increase in knowledge from the ignorance of the community around the Bogor Husada Stikes campus by using an assessment matrix in the form of a questionnaire conducted before and after the activity takes place whereby 43.3% increase in knowledge about borax, 83.3% increase in knowledge about how to identification of borax, and 85% increase in knowledge about the use of turmeric as a means of detecting borax. Keywords: Turmeric, curcumin, borax, food preservative, natural indicator. Abstrak Salah satu faktor makanan yang membahayakan adalah dengan ditemukannya boraks pada makanan. Boraks adalah bahan pengawet yang tidak diperuntukan untuk pengawet makanan. Kunyit mengandung senyawa kurkumin yang mampu menjadi indikator untuk mendeteksi boraks dengan parameter perubahan warna. Tujuan penelitian ini adalah untuk memberi pengetahuan kepada masyarakat sekitar kampus untuk memahami metode dini deteksi boraks pada Tanggal 1 Agustus 2022 dalam bentuk pengabdian kepada masyarakat Prodi S1 Farmasi rumpun keilmuan kimia farmasi. Metode yang digunakan yaitu ceramah dengan memberikan pemaparan materi terkait boraks dilanjutkan dengan demonstrasi cara mendeteksi boraks. Hasil pengabdian akan berdampak bagi pengetahuan masyarakat sekitar kampus Stikes Bogor Husada tentang identifikasi bahan makanan yang mengandung boraks agar mengurangi resiko paparan boraks dengan cara penggunaan kunyit yang mengandung kurkumin sebagai indikator alami deteksi boraks dengan memberikan indikator perubahan warna pada sampel makanan jika mengandung boraks. Kesimpulan dari kegiatan ini adalah ada peningkatan pengetahuan dari ketidak tahuan masyarakat sekitar kampus Stikes Bogor Husada dengan menggunakan matriks penilaian berupa kuisioner yang dilakukan sebelum dan sesudah kegiatan berlangsung dimana sebesar 43,3% peningkatan pengetahuan tentang boraks, sebesar 83,3% peningkatan pengetahuan tentang cara identifikasi boraks, dan sebesar 85% peningkatan pengetahuan tentang penggunaan kunyit sebagai cara mendeteksi boraks. Kata kunci: Kunyit, Kurkumin, Borak, Pengawet Makanan, Indikator Alami